уДачные самоделки. Новые идеи - Подольский Юрий Федорович (Клуб Семейного Досуга, 2012)
Экземпляры: ф-30 (20240506) / Инвентарный номер: 99482 / Цена: / Сис.шифр: 38. 71 / Авт.знак: П 44 / ББК: 38. 71